2019
DOI: 10.1038/s41419-019-1771-2
|View full text |Cite
|
Sign up to set email alerts
|

KHDRBS3 regulates the permeability of blood–tumor barrier via cDENND4C/miR-577 axis

Abstract: The existence of blood–tumor barrier (BTB) severely restricts the efficient delivery of antitumor drugs to cranial glioma tissues. Various strategies have been explored to increase BTB permeability. RNA-binding proteins and circular RNAs have recently emerged as potential regulators of endothelial cells functions. In this study, RNA-binding protein KH RNA-binding domain containing, signal transduction associated 3 (KHDRBS3) and circular RNA DENND4C (cDENND4C) were enriched in GECs. KHDRBS3 bound to cDENND4C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
0
35
1
Order By: Relevance
“…One of the mechanisms is that RBPs alter the stability of non-coding RNAs and regulate vascular endothelial function. For example, Wu et al [ 51] have reported that RBP KHDRBS3 binds to circRNA DENND4C, increases the circRNA's stability and upregulates the expression of tight junction-related proteins, thereby reducing the permeability of blood tumor barrier. Li et al [ 15] have reported that RBP ZRANB2 binds to the lncRNA and increases the lncRNA's stability, thereby affecting the functions of vascular ECs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms is that RBPs alter the stability of non-coding RNAs and regulate vascular endothelial function. For example, Wu et al [ 51] have reported that RBP KHDRBS3 binds to circRNA DENND4C, increases the circRNA's stability and upregulates the expression of tight junction-related proteins, thereby reducing the permeability of blood tumor barrier. Li et al [ 15] have reported that RBP ZRANB2 binds to the lncRNA and increases the lncRNA's stability, thereby affecting the functions of vascular ECs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-203 is upregulated in breast cancer and regulates cell growth and stemness via targeting SOCS3 [ 10 ]. Previously, a circRNA derived from DENN domain containing 4C (circ-DENND4C) has been newly recognized [ 13 ]. As a hypoxia-associated RNA, circ-DENND4C exhibited a high level and promoted cell proliferation in breast cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a hypoxia-associated RNA, circ-DENND4C exhibited a high level and promoted cell proliferation in breast cancer [ 14 ]. It was also reported that circ-DENND4C was involved in the regulation of blood-tumor barrier in glioma [ 13 ]. However, the function and mechanism of circ-DENND4C in HCC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms is that RBPs alter the stability of non-coding RNAs and regulate vascular endothelial function. For example, Wu et al [49] have reported that RBP KHDRBS3 binds to circRNA DENND4C, increases the circRNA's stability and upregulates the expression of tight junction-related proteins, thereby reducing the permeability of blood tumor barrier. Li et al [15] have reported that RBP ZRANB2 binds to the lncRNA and increases the lncRNA's stability, thereby affecting the functions of vascular ECs.…”
Section: Discussionmentioning
confidence: 99%